(untitled) (Applied Biological Research, 2015)
The present study was aimed to standardize tomato hybrid seed production technology. The experiment was laid out in a randomized block design with each treatment replicated three times. The female parent stigma was pollinated once and twice and the process continued for seven days after emasculation to know stigma receptivity and to standardize best pollination method for higher seed set. Highest stigma receptivity was observed one day after emasculation (71.11%) and it was lowest on 7th day after emasculation (43.33%). Repeated pollination showed highest efficiency of fruit set (75.25%) compared to 60.47% in single pollination. Repeated pollination resulted in more fruit set (80%) with pollinations on 1st & 2nd, 2nd & 3rd and 3rd & 4th days after emasculation. Later a drastic decrease in fruit set was observed. Method of pollination and stigma receptivity showed no significant effect on seed quality and storability even after twelve months of storage.